If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8x-8=5(x+5)
We move all terms to the left:
8x-8-(5(x+5))=0
We calculate terms in parentheses: -(5(x+5)), so:We get rid of parentheses
5(x+5)
We multiply parentheses
5x+25
Back to the equation:
-(5x+25)
8x-5x-25-8=0
We add all the numbers together, and all the variables
3x-33=0
We move all terms containing x to the left, all other terms to the right
3x=33
x=33/3
x=11
| 6/3x^2-11x-4-1/3=0 | | (x+7)•2=x-1 | | 4/3t+7=12 | | 20-4x=-60 | | 7x/4-5=23 | | -5=1/3k | | 81+c=45 | | 1/2a+2=5 | | 32k+4-8=60 | | 3/2(X+20)=2x+20 | | 5x+23=19 | | 7(x+2)-3(x-4)=30 | | 9x+3x-9x=6x+19-4x | | 2x-30=3x+90 | | 9(w+4)=-3w-48 | | 7x/4-5=33 | | 5.6=p-3.3 | | 7.x-10=3x | | 4x/2=22 | | n/3.2=-25/100 | | 5/6=x/13 | | 2b+5/2+3b=10 | | 9(w+4)=3w-48 | | 1/4m+2/3=4 | | 20(5^-2t)=10 | | -14=-6+2y | | 0=-(-9y) | | (16x-3)+(8x+15)+(4x-12)+(2x+6)=180 | | m+12+14-m+4m=2m+10 | | 11/27=4/9-2x3 | | 3(2x-3)(5x+7)=0 | | 6(4x-1=12(2x+3) |